Comparison of Scoring Systems for Prognosis in Cirrhotic Patients Admitted with Hepatic Encephalopathy - Mujahid, Muhammad Mamoon; Fazal, Imran; Siddiqi, Umair AhmEd; Waheed, Arsalan; Faheem, Muhammad; Mir, Abdul Wahab (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare various scoring systems to predict the prognosis in patients of cirrhosis presenting with hepatic encephalopathy at Pak Emirates Military Hospital Rawalpindi. Study Design: Cross-sectional study. Place and Duration: Gastroenterology Department, Pak Emirates Military Hospital Rawalpindi, from Sep 2018 to Feb 2019. Methodology: This study was conducted on 55 patients suffering from liver cirrhosis and presetting with hepatic encephalopathy at our hospital. Diagnosis of liver cirrhosis and hepatic encephalopathy was made by a consultant gastroenterologist based on clinical findings and relevant investigations. Chronic liver failure-sequential organ failure assessment (CLIF-SOFA), Model for end stage liver disease (MELD), and Child-Turcotte-Pugh (CTP) scores were calculated for all patients within the first 24 hours of presentation. Outcome in the study was patient either discharged or deceased at the end of study. Comparison was made between the three scores that which is a better predictor for prognosis of these patients. Results: Out of 55 patients included in the final analysis 35 were male and 20 were female. Commonest etiology of hepatic encephalopathy was Infection followed by Constipation.10 patients had grade 1 encephalopathy, 15 had grade 2, 20 had grade 3 while 10 had grade 4 encephalopathy. CLIF-SOFA emerged as better predictor for prognosis followed by MELD and CTP. Conclusion: CLIF-SOFA was the best of all scores in predicting the prognosis of patients suffering from liver cirrhosis presenting with hepatic encephalopathy. MELD and CTP were also significant in this regard but less as compared to CLIFSOFA.